Board Governance Attributes and ESG Disclosure: Evidence from Non-Financial Companies Listed on the Indonesia Stock Exchange - Nadiah Humairah Adani; Marsono Marsono (JURNAL AKUNTANSI DAN AUDITING, 2026)
This study aims to test and find empirical evidence of the influence of corporate governance on ESG disclosure. The corporate governance factors used include board size, gender diversity, the proportion of independent board members, and institutional ownership structure. The control variables used in this study include firm size, leverage, and profitability (ROA). The dependent variable in this study, ESG disclosure, is measured using ESG scores provided by the Bloomberg database. The study population consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The total sample used in this study consists of 112 companies selected through purposive sampling based on predetermined criteria. The analysis technique employed is panel data regression, given the number of companies and the observation years used in this study. The results of this study indicate that board size and institutional ownership have a negative effect on ESG disclosure. Meanwhile, other attributes do not have a relationship with ESG disclosure. These findings imply the need to review corporate governance structures to promote transparency in ESG disclosure in Indonesia.